PENGARUH STRATEGI PREDICTION GUIDE TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS VIII SMP UTAMA 3 BANDAR LAMPUNG - Aty Nurdiana; Arinta Rara Kirana (Prodi Pendidikan Matematika, STKIP PGRI Bandar Lampung, 2020)
The problems that were examined in this research pertaining to less account of the results that students are learning mathematics. The purpose of this research is to find the learning strategy guide prediction for the students learn math ability of class VIII of SMP UTAMA 3 Bandar Lampung in the academic year 2018/2019. The research uses experimental methods to the population in this research is all students ability of class VIII of SMP UTAMA 3 Bandar Lampung, its consisting of 3 class to the total number of 83 students, The sample was taken two classes viii-b class as a class the experiment apply prediction guide strategy And viii-c class as a class control a conventional learning. Sample taken using a technique clusters of random sampling. To know mathematics students writer test in the form of an essay as many as 10 the first has been tested validity and reliability. The testing of hypotheses on this research using formulas t-hit. The results of the testing of hypotheses using formulas statistic t-hit = 9,40 obtained the t. From table distribution t on significant standard known t = 5 % = 2,00 then so which means the average learning outcomes mathematics students who use prediction guide strategy be higher than the average learning outcomes mathematics students who use conventional kind of classroom From the above it can be concluded guide prediction that strategy can and have had a positive impact of the results of learn math.